СТИМуЛюВАННЯ ПРОРОСТАННЯ НАСІННЯ ПЕЛюШКИ бІОПРЕПАРАТАМИ ВІТчИЗНЯНОгО ВИРОбНИЦТВА - Вишневська , О.В.; Маркіна , О.В. (Institute of Agrocultural Microbiology and Agro-industrial Manufacture of NAAS of Ukraine, 2013)
The paper covers the research results of biological inoculation effect on field pea Pisum arvense seeds germination under different temperature regimes. The optimum temperatures ensuring high seeds germination rates were defined. It was established that Rhizohumin have showed the best results by the efficiency coefficient of biological preparation use on the early stages of plant development.